Body Mass Index (BMI) and Dental Caries Experience among Children of Eastern Region of Nepal - Bhagat, Tarakant; Shrestha, Ashish; Agrawal, Santosh Kumari (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Introduction: Dental caries and obesity share some common, modifiable influences such as diet and lifestyle including changes in physical activity and food characters. So, obesity can be considered as a predictor of dental caries and various studies have shown the positive association between these two factors. Objective: The study aims to analyze the relationship between dental caries and BMI in children of eastern region of Nepal. Methods: A cross-sectional study design was used comprising 600 school children in eastern region of Nepal. Anthropometric measures for the calculation of Body Mass Index (BMI), occurrence of dental caries, missing, and filled teeth due to caries in both the primary and permanent dentition (dft and DMFT respectively) were collected. Data were analyzed using Spearman’s correlation and independent t test to assess correlation between dental caries and BMI. Results: Dental caries prevalence was 57.3%. The difference in caries experience among gender was insignificant (p = 0.172). Caries experience decreased significantly with increase in years of schooling (p = 0.002) and with increase in age (p < 0.001). Caries experience increased with an increase in BMI but was not significant (p = 0.199). There was a positive correlation between BMI and DMFT /DMFS but was not statistically significant. The correlation between dft and dfs was statistically significant. Conclusions: The study indicated that some form of correlation existed between BMI and dental caries but the association was weak. Healthy with age children experience more caries than overweight and underweight children.